Effect of Compressive Strain Rates on Viscoelasticity and Water Content in Intact Porcine Stomach Wall Tissues - Udayamohan, Vijay Shashank; Byju, Achu Geetha; Harris, Jason L; Haridas, Balakrishna (Journal of biomechanical engineering, 2025)
Laparoscopic staplers are used extensively to seal and transect tissue. These devices compress tissue between the stapler jaws to achieve a desired compressed tissue thickness in preparation for stapling. The extent and rate of compression are dependent on surgeon technique, tissue characteristics, and stapler type, all of which can impact stapling outcomes such as bleeding, staple line leaks, and tissue healing. Historically, surgeons have relied on their experience, training, and tactile feedback from the device to optimize stapling. In recent years, the transition to electromechanical and robotic staplers has greatly impacted the tactile feedback available to the surgeon. This raises new questions about the optimal rates of tissue compression and the resultant tissue forces. This study quantifies the transmural biomechanics of the porcine stomach wall. Multirate indentation tests were used to observe the effects of indentation rate on the viscoelastic behavior of the stomach tissue during indentation, stress relaxation, and unconstrained recovery. Results show that the stomach wall demonstrates higher stress relaxation (88% versus 80%) and greater strain recovery (52% versus 47%) when indented at high rates (37.5%/s) versus slow rates (7.5%/s). Additionally, water content analysis was used to study fluid flow away from indented regions. Unindented regions were found to have greater water content compared to indented regions (78% compared to 75%). This data generated in this study may be used to enable the development of constitutive models of stomach tissue, which in turn may inform the control algorithms that drive compressive surgical devices.